"The Cock of Liberty medaillon struck for the LCS on the release of Daniel Eaton, who is referred to on the back of the medaillon (1795)
"The Cock of Liberty medaillon struck for the LCS on the release of Daniel Eaton, who is referred to on the back of the medaillon.